BRAF V600E mutation in metastatic colorectal cancer: Methods of detection and correlation with clinical and pathologic features. Issue 8 (2nd August 2016) - Roma, Cristin; Rachiglio, Anna Maria; Pasquale, Raffaella; Fenizia, Francesca; Iannaccone, Alessia; Tatangelo, Fabiana; Antinolfi, Giuseppe; Parrella, Paola; Graziano, Paolo; Sabatino, Lina; Colantuoni, Vittorio; Botti, Gerardo; et al.
ABSTRACT: The screening for BRAF V600E mutation is employed in clinical practice for its prognostic and potentially predictive role in patients with metastatic colorectal carcinoma (mCRC). Little information is available on the sensitivity and specificity of the testing methods to detect this mutation in CRC. By using serial dilution of BRAF mutant DNA with wild type DNA, we found that the sensitivity of allelic discrimination-Real Time PCR was higher than PCR-Sequencing (10% vs 20%). In agreement, the Real Time PCR assay displayed increased analytical sensitivity in detecting the BRAF V600E mutation as compared with PCR-Sequencing in a cohort of 510 consecutive CRCs (21 vs 16 cases). Targeted resequencing demonstrated that all cases negative by PCR-Sequencing had an allelic frequency of the BRAF mutation <20%, thus suggesting tumor heterogeneity. The association of BRAF mutations with clinical and pathological features was assessed next in a cohort of 840 KRAS exon 2 wild type CRC patients screened with the Real Time PCR assay. The BRAF V600E mutation frequency in this cohort was 7.8% that increased to 33.4% in females over 70 y of age with right-sided tumor location. BRAF mutations were also detected in 4.4% of male patients with left-sided tumors and aged <70 y. Fourteen of 61 (22.9%) BRAF V600E mutation bearing patients exhibited microsatellite instability (MSI) as assessed by T17 mononucleotide sequence within intron 8 of HSP110. Our study indicates that Real Time PCR-based assays are more sensitive than PCR-Sequencing to detect the BRAF V600E mutation in CRC and that BRAF mutations screening should not be restricted to selected patients on the basis of the clinical-pathological characteristics.